Efficacy and safety of troglitazone in the treatment of lipodystrophy syndromes - Arioglu, E; Duncan-Morin, J; Sebring, N; Rother, K I; Gottlieb, N; Lieberman, J; Herion, D; Kleiner, D E; Reynolds, J; Premkumar, A; Sumner, A E; Hoofnagle, J; et al. (Annals of internal medicine, 2000)
Troglitazone promotes adipocyte differentiation in vitro and increases insulin sensitivity in vivo. Therefore, troglitazone may have therapeutic benefit in lipoatrophic diabetes. To determine whether troglitazone ameliorates hyperglycemia and hypertriglyceridemia or increases fat mass in lipoatrophic patients. Open-labeled prospective study. United States and Canada. 20 patients with various syndromes associated with lipoatrophy or lipodystrophy. 6 months of therapy with troglitazone, 200 to 600 mg/d. Levels of hemoglobin A1c triglycerides, free fatty acids, and insulin; respiratory quotient; percentage of body fat; liver volume; and regional fat mass. In the 13 patients with diabetes who completed 6 months of troglitazone therapy, hemoglobin A1c levels decreased by a mean of 2.8% (95% CI, 1.9% to 3.7%; P < 0.001). In all 19 study patients, fasting triglyceride levels decreased by 2.6 mmol/L (230 mg/dL) (CI, 0.7 to 4.5 mmol/L [62 to 398 mg/dL]; P = 0.019) and free fatty acid levels decreased by 325 micromol/L (CI, 135 to 515 micromol/L; P = 0.035). The respiratory quotient decreased by a mean of 0.12 (CI, 0.08 to 0.16; P < 0.001), suggesting that troglitazone promoted oxidation of fat. Body fat increased by a mean of 2.4 percentage points (CI, 1.3 to 4.5 percentage points; P = 0.044). Magnetic resonance imaging showed an increase in subcutaneous adipose tissue but not in visceral fat. In one patient, the serum alanine aminotransferase level increased eightfold during the 10th months of troglitazone treatment but normalized 3 months after discontinuation of treatment Liver biopsy revealed an eosinophilic infiltrate, suggesting hypersensitivity reaction as a cause of hepatotoxicity. Troglitazone therapy improved metabolic control and increased body fat in patients with lipoatrophic diabetes. The substantial benefits of troglitazone must be balanced against the risk for hepatotoxicity, which can occur relatively late in the treatment course.